Cervical schwannoma: diagnosis and treatment - Sulakhe, Amol; Save, Sneha; Kumar, Ravish (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Schwannomas are benign, encapsulated, slow-growing, tumours deriving from the peri neural cells located in the nerve sheath. They can arise from any cranial, peripheral or autonomic nerves, and show a predilection for the head and neck region. They may produce secondary symptoms like nasal obstruction, dysphagia, and hoarseness of voice depending upon the location of the tumour. Preoperative diagnosis is difficult, relying on clinical suspicion, and confirmed by surgical pathology. Preoperative imaging or fine needle aspiration cytology may help to reveal diagnosis. The definitive diagnosis is made by histopathological examinations. A 28 years old female patient presented to the OPD with painless swelling on the left lateral side of the neck since 1 year. The swelling was mobile, non-tender, non-pulsatile firm in consistency measuring 4×3 cm with no bruit. MRI neck with contrast was done which revealed a moderately enhancing lesion of size 7×4×3 cm in the left carotid sheath. The tumour was approached by an anterior approach along the medial border of the sternocleidomastoid. Platysma and fascia were dissected followed by carotid sheath to reach the tumour. As the mass was seen arising from a branch of the ansa cervicalis, it had to be sacrificed.